2019
DOI: 10.3390/ani9121151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Activated Charcoal-Herb Extractum Complex on Antioxidant Status, Lipid Metabolites and Safety of Excess Supplementation in Weaned Piglets

Abstract: This study was aimed at evaluating the effects of activated charcoal-herb extractum complex (CHC) on antioxidant status, serum lipid metabolites and its safety supplement in weaning piglets. In experiment 1, a total of 216 piglets (Duroc × Landrace × Large White) weaned at 28 days of age with initial body weight of 8.55 ± 1.18 kg were assigned randomly to six treatment groups. each treatment group had six pens, with six pigs per pen. Pigs were fed a corn-soybean meal-based diet supplemented with 500, 1000, 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
2
2
0
Order By: Relevance
“…The present study on broilers confirmed the finding that supplementing feed with PFAC could induce a positive effect on cholesterol production compared to CON ( 31 ), but not with AC. Although the serum biochemistry differed among the treatments, the values were all within the normal reference range for broilers ( 54 , 55 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The present study on broilers confirmed the finding that supplementing feed with PFAC could induce a positive effect on cholesterol production compared to CON ( 31 ), but not with AC. Although the serum biochemistry differed among the treatments, the values were all within the normal reference range for broilers ( 54 , 55 ).…”
Section: Discussionsupporting
confidence: 89%
“…In our previous studies, herbal extract was coupled with activated charcoal to form a charcoal-herb complex for feeding piglets and broilers. We found that the charcoal-herb complex promoted growth performance, enhanced body immunity, reduced inflammation, and improved antioxidant status (29)(30)(31)(32). Four types of Chinese medicine were used according to their specific functions reported in the scientific literature (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MDA is a suitable marker to reflect the damage degree of free radicals to the organism, and SOD is essential for the improvement of general redox and maintenance of intracellular homeostasis. 21 As expected, the serum MDA concentration was obviously suppressed and the SOD activity was elevated by Gal-1 pre-treatment in myocarditis mice. Consistently, pre-treatment with Gal-1 decreased the fluorescence intensity of ROS in vitro .…”
Section: Discussionsupporting
confidence: 71%